Grinding aid for producing regenerated composite admixture by using construction waste and preparation method of grinding aid
By using abrasive agent composed of raw materials such as modified triethanolamine mother liquor, the problems of poor effect and high cost in the prior art are solved, and efficient and economical grinding effect of regeneration composite blends are achieved, and the materials are improved strength and activity.
Patent Information
- Application Number
- CN202310998327.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the abrasive agent used for the production and regeneration composite admixture of construction waste is not satisfactory, the consumption cost is high, and the activation ability is poor.
The agitator composed of modified triethanolamine mother liquor, diethylene glycol, sodium thiochlorate, diethanol monoisopropanolamine and calcium liquorate was used to combine it through the preparation method of modified triethanolamine mother liquor to form The polymer with cross-linking activity improves the adsorption ability and compatibility of the abrasive agent.
The rapid synthesis of grinding aids under normal temperature and pressure is achieved, the preparation process is simplified, the specific surface area and activity of composite blends is improved, the grinding efficiency and refinement degree is enhanced, the power consumption is reduced, and the early material is improved. Later intensity.
Smart Images

Figure CN119461931A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of recycled composite admixture production, in particular to a grinding aid for producing recycled composite admixture using construction waste and a preparation method thereof. Background Art
[0002] With the continuous development of urban construction, waste has also increased, and the recycling of construction waste has become an inevitable trend. The construction waste mentioned in this article refers to the waste concrete, mortar, bricks and tiles, glass, ceramics, abandoned soil, etc. generated during the construction, reconstruction, expansion and demolition of various buildings, structures, pipe networks, etc. by construction units and construction units, as well as the waste generated during the decoration and renovation of houses by residents.
[0003] At present, my country is in a period of rapid urbanization. Urban expansion and reconstruction, shantytown reconstruction, etc. have generated a large amount of construction waste, which has contributed to the "garbage siege". Construction waste should not only be harmlessly treated, but also be recycled as a resource, otherwise it will be difficult to truly solve the problem in essence. The practices of other developed countries and regions have shown that construction waste is usable material and a resource that has been placed in the wrong place. The most effective and suitable field for the recycling of construction waste is the building materials industry.
[0004] In the Chinese invention patent with the patent publication number CN111153617A, entitled A recycled composite admixture using construction waste and a preparation method thereof, a grinding aid needs to be added during the roller press grinding process to improve the grinding efficiency, reduce the powder resistance and prevent the aggregation of particles. Although there are also many grinding aids in the prior art, their effects are not satisfactory.
[0005] For example, in the Chinese invention patent with the patent publication number of CN108516842A and the name of a ceramic grinding aid, it includes: 10 to 15 parts of sodium tripolyphosphate, 8 to 13 parts of sodium carbonate, 15 to 20 parts of sodium oxalate, 8 to 15 parts of polyacrylic acid, 20 to 30 parts of delta-layered crystalline sodium disilicate, 15 to 20 parts of pyrophyllite powder, 200 to 500 parts of grinding aid base and 60 to 120 parts of dispersing aid. It uses diisopropanolamine, diethanolamine and succinic anhydride as raw materials, and then forms a hyperbranched polymer through esterification reaction. The ends of the hyperbranched polymer contain a large number of polar groups such as hydroxyl groups and ester groups, which are easily adsorbed on the surface of ceramic clinker to form hydrogen bond film, hinder the healing of microcracks, and improve the grinding efficiency. The intermediate product is synthesized by chlorination of xylitol and acryloyl chloride. The intermediate product partially replaces methyl allyl polyoxyethylene ether and is prepared by free radical polymerization with hydroxyethyl methacrylate and acrylic acid under the action of ammonium persulfate. The fluidity of the ceramic slurry is enhanced, the grinding aid effect is improved, and the flow rate of the material in the mill and the electrostatic adsorption problem in the mill are effectively improved. Among them, the technical characteristics of the ceramic grinding aid are as follows: one is the amide reaction (R-CO-ANHYDRIDE+R'NH2->R-CO-NHR'+R'COOH, wherein R and R' represent organic groups respectively). Although it has many advantages, side reactions may occur, such as decomposition, dehydration, hybridization, etc., resulting in impure products or reduced yields, slow reaction rates, and high thermal sensitivity. The second is the acyl chloride reaction (RCOOH+PCl5->RCOCl+POCl3+HCl), which is characterized by containing an acyl group (C=O bond) in the molecule and a halogen atom or a halogen-like group connected to the carbon. Although this type of substance has its advantages, it is usually highly toxic and corrosive, and has certain hazards to the human body and the environment. Secondly, side reactions may occur during the reaction, such as over-chlorination, olefin digestion and decomposition, etc., resulting in reduced yield or impure products. Finally, the acyl chloride reaction may not be applicable to some functional groups and functional groups that are sensitive to chlorinating agents, and it is easy to undergo hydrolysis in moisture or water to generate the corresponding acid, which has poor stability.
[0006] In addition, in the Chinese invention patent "Patent Publication No.: CN111822137A, Name: Mineral Composite Powder Grinding Aid", it includes: 8-13 parts of water, 46-56 parts of triethanolamine, 18-23 parts of diethylamine, 13-18 parts of grinding aids, and 4-6 parts of promoting coupling agent; when preparing the mineral composite powder grinding aid, diethylamine is uniformly dripped into the mixture of water, triethanolamine, and grinding aids, and the dripping time is controlled within 1 hour. When preparing the mineral composite powder grinding aid, the promoting coupling agent is uniformly dripped into the mixture of water, triethanolamine, and grinding aids, and the dripping time is controlled within 2 hours. Although the grinding aid in the above patent can play a certain grinding aid effect in the treatment of industrial solid waste and urban construction waste, it consumes a large proportion of triethanolamine and has a high cost, which is not conducive to actual production application and promotion. As for the production of recycled composite admixtures specifically using construction waste, its activation ability is poor and it cannot effectively and reliably assist grinding.
[0007] Therefore, there is an urgent need to propose a grinding aid for producing recycled composite admixtures using construction waste that is simple to prepare, has reliable performance, and has cost advantages. Summary of the invention
[0008] In view of the above problems, the purpose of the present invention is to provide a grinding aid for producing a regenerated composite admixture using construction waste and a preparation method thereof. The technical solution adopted by the present invention is as follows:
[0009] The grinding aid for producing recycled composite admixtures using construction waste is composed of the following raw materials in percentage by mass:
[0010] 10% to 20% modified triethanolamine mother liquor;
[0011] 1% to 5% diethylene glycol;
[0012] 1% to 5% sodium thiochloride;
[0013] 1% to 5% diethanol monoisopropanolamine;
[0014] 1% to 5% calcium lignosulfonate;
[0015] The balance is water.
[0016] Furthermore, the modified triethanolamine mother solution is prepared from the following raw materials in parts by weight:
[0017] 20-25 parts of triethanolamine;
[0018] 5-10 parts of triisopropanolamine;
[0019] 5-10 parts of epichlorohydrin;
[0020] 12 to 15 parts of a sodium hydroxide aqueous solution having a concentration of 40% by mass.
[0021] A method for preparing a grinding aid for producing a regenerated composite admixture using construction waste comprises the following steps:
[0022] preparing a modified triethanolamine mother solution;
[0023] 10% to 20% of modified triethanolamine mother liquor, 1% to 5% of diethylene glycol, 1% to 5% of sodium thiochlorate, 1% to 5% of diethanol monoisopropanolamine, 1% to 5% of calcium wood sulfonate and water are uniformly mixed to obtain a grinding aid.
[0024] Furthermore, the preparation method of the modified triethanolamine mother solution comprises the following steps:
[0025] Add 20-25 parts of triethanolamine and 5-10 parts of triisopropanolamine into a reaction vessel and stir evenly;
[0026] Add 5 to 10 parts of epichlorohydrin into a constant pressure dropper, and add 12 to 15 parts of a sodium hydroxide aqueous solution with a mass percent concentration of 40% into another constant pressure dropper;
[0027] Open two constant pressure droppers at the same time, and drip epichlorohydrin and sodium hydroxide aqueous solution into the reaction container at the same time, stir, and react at 45±5°C for 1.0 to 2 hours to obtain a reactant;
[0028] The reactants are dried, and the upper liquid is the modified triethanolamine mother liquor.
[0029] Furthermore, the reactants are dried by evaporating water in the reactants at 80±10° C. and a pressure of 60±20 Pa.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The grinding aid of the present invention does not require any heating, pressurizing or vacuuming equipment during the preparation process, and can react at room temperature and pressure. The synthesis cycle is short, the operation is simple and easy, the feasibility is high, the reaction rate is fast, the synthesis yield is high, and the final product does not need to undergo any separation or filtering treatment.
[0032] (2) The present invention uses modified triethanolamine N(CH2CH2OH)3 as the mother liquor, and the amount of modified triethanolamine (-OH) is increased. During the synthesis process, the monomer with cross-linking activity forms cross-linking points on the polymer molecular chain, forming branching of the molecular chain. These cross-linking points connect the polymer chains together through cross-linking, forming covalent bonds on the main chain, and forming a branching structure. After compounding (i.e., the grinding aid preparation process), when grinding the composite admixture, due to its unique molecular structure, it can reduce the friction between particles during the grinding process, help the particles to slide or roll more smoothly to prevent the aggregation and accumulation of particles, thereby changing the surface charge and chemical properties of the fine particles to promote effective collision and grinding between particles, so as to enhance the particle grinding efficiency and refinement degree, and grind the specific surface area of the composite admixture produced by using construction waste to be higher on the basis of the original grinding energy consumption, so as to achieve the purpose of enhancing and improving the activity, and effectively improve the early and late strength of the composite admixture.
[0033] (3) A certain amount of diethanol monoisopropanolamine is compounded in the grinding aid of the present invention, and its purpose is to utilize the cross-linking effect formed between polyhydroxy substances to improve the adsorption capacity of the grinding aid. In addition, the purpose of compounding sodium thiochlorate and calcium lignosulfonate is to adjust the compatibility of the grinding aid, and it has a certain reinforcing effect and can also play a role in reducing product costs. After the grinding aid is mixed, the specific surface area of the composite admixture can be effectively increased, so that the overlapping of fine particles causes lattice distortion and deformation, and solid friction and deformation occur inside the particles, thereby improving activity and fluidity, and avoiding agglomeration and paste grinding during the grinding process.
[0034] In summary, the present invention has the advantages of simple preparation, reliable performance, etc., and has high practical value and promotion value in the technical field of recycled composite admixture production. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope of protection. For those skilled in the art, other related drawings can be obtained based on these drawings without creative work.
[0036] Figure 1 The figure is a reaction process diagram for preparing the modified triethanolamine mother liquor of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of this application clearer, the present invention is further described below in conjunction with the accompanying drawings and embodiments, and the embodiments of the present invention include but are not limited to the following embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0038] In this embodiment, the term "and / or" is merely a term used to describe the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone.
[0039] The terms "first" and "second" in the description and claims of this embodiment are used to distinguish different objects rather than to describe a specific order of objects. For example, a first target object and a second target object are used to distinguish different target objects rather than to describe a specific order of target objects.
[0040] In the embodiments of the present application, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.
[0041] In the description of the embodiments of the present application, unless otherwise specified, the meaning of "multiple" refers to two or more than two. For example, multiple processing units refer to two or more processing units; multiple systems refer to two or more systems.
[0042] like Figure 1 As shown, this embodiment provides a grinding aid for producing recycled composite admixtures using construction waste and a preparation method thereof, wherein the grinding aid is prepared by taking the raw materials of each component in mass percentage from 20% to 30% of modified triethanolamine mother liquor, 1% to 5% of diethylene glycol, 1% to 5% of sodium thiocyanate, 1% to 5% of diethanol monoisopropanolamine, 1% to 5% of calcium lignosulfonate and the balance of water. The modified triethanolamine mother liquor, diethylene glycol, sodium thiocyanate, diethanol monoisopropanolamine, calcium lignosulfonate and water are mixed to obtain the grinding aid.
[0043] The preparation method of the modified triethanolamine mother liquor is as follows: 20 to 25 parts by mass of triethanolamine, 5 to 10 parts by mass of triisopropanolamine, 5 to 10 parts by mass of epichlorohydrin, and 12 to 15 parts by mass of a sodium hydroxide aqueous solution with a mass percentage concentration of 40%, the triethanolamine and triisopropanolamine are put into a reaction container (such as a three-necked flask) with a stirring device, the epichlorohydrin is added to a constant pressure dropper, the sodium hydroxide aqueous solution is added to another constant pressure dropper, the two constant pressure droppers are opened at the same time, the epichlorohydrin and the sodium hydroxide aqueous solution are (slowly) dripped into the reaction container and stirred, and the reaction temperature is controlled to be 45±5°C; after the dripping is completed, the reaction is continued for 1 to 2 hours; the reaction product is poured into a container and placed in a vacuum drying oven to evaporate and remove the water therein, precipitate NaCl, and the upper layer of liquid is taken as the prepared modified triethanolamine mother liquor, and the reaction is as follows Figure 1 As shown, the reaction process in which triisopropanolamine participates is similar to that of triethanolamine, which will not be described in detail here.
[0044] This embodiment provides 6 comparative cases:
[0045] Sample 1 (JZ-1)
[0046] The grinding aid sample 1 is numbered as JZ-1, and its composition is: 20% of modified triethanolamine mother liquor, 5% of diethanol monoisopropanolamine, 3% of diethylene glycol, 3% of sodium thiochlorate, 2% of calcium wood sulfonate and 67% of water.
[0047] The preparation process of grinding aids has the following steps:
[0048] (1) Preparation process of modified triethanolamine mother liquor:
[0049] 20-25 parts by weight of triethanolamine, 5-10 parts by weight of triisopropanolamine, 5-10 parts by weight of epichlorohydrin, and 12-15 parts by weight of a sodium hydroxide aqueous solution with a mass percentage concentration of 40% are added to a reaction vessel (three-necked flask) with a stirring device, epichlorohydrin is added to a constant pressure dropper, and a sodium hydroxide aqueous solution is added to another constant pressure dropper. The two constant pressure droppers are opened at the same time, and epichlorohydrin and the sodium hydroxide aqueous solution are slowly dropped into the reaction vessel and stirred, and the reaction temperature is controlled to be 45±5°C; after the dropwise addition is completed, the reaction is continued for another 1-2 hours, and the reaction product is poured into a container and placed in a vacuum drying oven to evaporate and remove water therein, and NaCl is precipitated, and the upper layer of liquid is taken as the prepared modified triethanolamine mother liquor.
[0050] (2) 20% by mass of modified triethanolamine mother liquor, 5% of diethanol monoisopropanolamine, 3% of diethylene glycol, 3% of sodium thiochlorate, 2% of calcium wood sulfonate, and 67% of water are compounded and mixed to obtain a grinding aid for producing recycled composite admixtures using construction waste.
[0051] In this embodiment, the ratio table of samples 1 to 6 (ie, numbers JZ-1 to JZ-6) is shown in Table 1.
[0052] Table 1 Proportions of samples 1 to 6
[0053]
[0054] The grinding aid for producing recycled composite admixture was prepared according to the proportions in Table 1, and a small grinding experiment was carried out. The construction waste and other raw materials used in the experiment were all from a grinding plant in Sichuan, and their chemical composition and mass percentage content are shown in Table 2.
[0055] Table 2 Chemical composition and mass percentage of construction waste and other raw materials in a grinding plant in Sichuan
[0056]
[0057] According to the above raw materials and the same ratio of composite admixtures, a small mill comparison experiment was carried out using the above-mentioned grinding aids numbered JZ-1 to JZ-6. The ingredients and grinding process are as follows: the construction waste crushed by a jaw crusher: lithium slag: electric furnace slag: fly ash = 85:5:5:5 are mixed, and then 0.125% of each type of grinding aid JZ-1 to JZ-6 are added respectively. After mixing, put into a φ500×500mm experimental mill for grinding, and the grinding time of the samples with and without grinding aids is the same. Each mill is equipped with 5 kg of ingredients. The grinding time is based on the sample without grinding aids. The powder is ground to a specific surface area of 650±30 m2 / Kg. Then, the composite blended powder after adding grinding aids is compared with the specific surface area, 45μm sieve residue, fluidity, particle size distribution and activity comparison test. The activity test is carried out according to the mortar strength test after mixing the standard cement 70% + 30% blended powder. The 7-day strength of the benchmark cement is: 39.5MPa, and the 28-day strength is: 52.0MPa. The specific data are shown in Table 3.
[0058] Table 3 Comparison of flexural strength, compressive strength and activity index
[0059]
[0060] In this embodiment, when the dosage is 0.125% and the water-cement ratio is the same as that of the control group, the activity of the composite admixture produced by using construction waste for 28 days can effectively increase and reduce the clinker consumption by about 4%; because the modified triethanolamine has many functional group binding points, it is very easy to adsorb on the surface of the construction slag particles to form an adsorption film, so it can effectively improve the activity of the composite admixture produced by using construction waste, and the activity is prolonged with the increase of the dosage. When the dosage is 0.125%, the activity of the admixture can be about 4% higher than that of the control group.
[0061] Through the above comparative experiments, when the grinding aid is added, the composite admixture is fully ground during the grinding process, the grinding time is shorter than that of the blank sample, and the 45-micron sieve residue is decreasing when the relative ratio is close. It is proved that in actual production, if the grinding aid is added, it is also positive to increase production and reduce power consumption. The purpose of using grinding aids is mainly to improve and stabilize the grinding process, implement high-fine grinding and ultra-fine grinding, meet standard requirements, increase mill output, improve powder performance, save power consumption, etc., so that production enterprises can obtain comprehensive economic benefits.
[0062] In order to understand the particle size distribution of the above experimental samples, they were tested using a particle size analyzer. The specific data are shown in Table 4.
[0063] Table 4 Particle size distribution of samples
[0064]
[0065] Compared with the particle distribution of the composite admixtures without grinding aids, the distribution of 3-32 μm increased from 40.3% to 58.9% when the composite admixtures were ground with grinding aids, which shows that the grinding aids play an important role in improving the grindability and deformation energy of the particles. Therefore, in order to improve the output and activity of the composite admixtures produced by construction waste and ensure the effective production of fine powder, from the perspective of increasing production, saving electricity and saving comprehensive energy, high-quality composite admixture grinding aids should be vigorously promoted and actively adopted. The grinding aids used in the production of composite admixtures with construction waste in this embodiment have an important influence on the pore volume, surface and particle distribution. In the actual production and grinding process, when there is no grinding aid, more and more unsaturated valence bonds and structural units with positive and negative charges will be formed on the surface of the microparticles, making the particles in an unstable high-energy state. The surface energy of the particles also increases rapidly, and the group of microparticles forms agglomerates that are difficult to disperse again under the action of relatively large mutual attraction. The reagglomeration of particles causes a reduction in grinding output and an increase in power consumption. After the grinding aid is added to the composite admixture produced from construction waste, the friction between particles is reduced, which helps the particles to slide or roll more smoothly to prevent the aggregation and accumulation of particles, thereby changing the surface charge and chemical properties of fine particles, promoting effective collision and grinding between particles, so as to enhance the grinding efficiency and refinement of particles, and grind the composite admixture produced from construction waste to a finer degree on the basis of the original grinding energy consumption, so as to achieve the purpose of strengthening and improving the activity, and effectively improve the early and late strength of the composite admixture. While maintaining the original mill output, the strength of the composite admixture can be increased by 2-5MPa.
[0066] In order to understand the performance of the above experimental samples in concrete, cement, sand, gravel and admixtures from the local commercial mixing station were used to replace fly ash in equal proportions for concrete comparative mixing. The specific trial mixing conditions are shown in Table 5.
[0067] Table 5 Concrete comparison test mixing
[0068]
[0069] Comparing the performance of concrete with and without grinding aids, the water demand of concrete increased relatively after the grinding aids were added, but it was still within the water requirement of the mix ratio. The initial state of the concrete was good, with good workability and fluidity. After 2 hours, the concrete showed a certain degree of loss. Relatively speaking, the loss of the mixed powder with grinding aids was slightly greater than that of the blank sample. This can be met by adjusting the admixtures to meet the use requirements. From the perspective of concrete strength, the concrete strength of the mixed powder with different proportions of grinding aids was improved to varying degrees compared with the blank sample.
[0070] The invention patent of the grinding aid for producing recycled composite admixtures from construction waste has been put into large-scale production and application in local grinding stations after laboratory demonstration. After the grinding aid for producing recycled composite admixtures is added, the grinding conditions are improved, the circulation load is reduced, the powder selection efficiency is improved while maintaining the original quality standards. It can also reduce the power consumption of pneumatic conveying of composite admixtures, which can increase the mill output by about 5%, save 2-3kWh / t of electricity, and bring economic and social benefits to the enterprise.
[0071] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any changes that adopt the design principles of the present invention and are made through non-creative labor on this basis should fall within the protection scope of the present invention.
Claims
1. A grinding aid for producing recycled composite admixtures using construction waste, characterized in that: It is composed of the following raw materials in percentage by weight: 10% to 20% modified triethanolamine mother liquor; 1% to 5% diethylene glycol; 1% to 5% sodium thiochloride; 1% to 5% diethanol monoisopropanolamine; 1% to 5% calcium lignosulfonate; The balance is water.
2. The grinding aid for producing recycled composite admixtures using construction waste according to claim 1, characterized in that: The modified triethanolamine mother solution is prepared from the following raw materials in parts by weight: 20-25 parts of triethanolamine; 5-10 parts of triisopropanolamine; 5-10 parts of epichlorohydrin; 12 to 15 parts of a sodium hydroxide aqueous solution having a concentration of 40% by mass.
3. A method for preparing a grinding aid for producing a regenerated composite admixture using construction waste according to any one of claims 1 to 2, characterized in that: The following steps are involved: preparing a modified triethanolamine mother solution; 10% to 20% of modified triethanolamine mother liquor, 1% to 5% of diethylene glycol, 1% to 5% of sodium thiochlorate, 1% to 5% of diethanol monoisopropanolamine, 1% to 5% of calcium wood sulfonate and water are uniformly mixed to obtain a grinding aid.
4. The method for preparing a grinding aid for producing a regenerated composite admixture using construction waste according to claim 3, characterized in that: The preparation method of the modified triethanolamine mother solution comprises the following steps: Add 20-25 parts of triethanolamine and 5-10 parts of triisopropanolamine into a reaction vessel and stir evenly; Add 5 to 10 parts of epichlorohydrin into a constant pressure dropper, and add 12 to 15 parts of a sodium hydroxide aqueous solution with a mass percent concentration of 40% into another constant pressure dropper; Open two constant pressure droppers at the same time, and drip epichlorohydrin and sodium hydroxide aqueous solution into the reaction container at the same time, stir, and react at 45±5°C for 1.0 to 2 hours to obtain a reactant; The reactants are dried, and the upper liquid is the modified triethanolamine mother liquor.
5. The method for preparing a grinding aid for producing a regenerated composite admixture using construction waste according to claim 4, characterized in that: During the drying of the reactants, water in the reactants is evaporated and removed under the conditions of 80±10° C. and a pressure of 60±20 Pa.
Citation Information
Patent Citations
Ceramic grinding aid
CN108516842A
Regenerated composite admixture utilizing construction waste and preparation method thereof
CN111153617A
Mineral composite powder grinding aid
CN111822137A